Nanoparticles in bioimaging - GOUNKO, IOURI (My University, 2016)
This Special Issue of Nanomaterials is dedicated to the application of nanoparticulate materials in biological imaging. The issue highlights the rapidly expanding uses and interest in nanomaterials for bioapplications; in particular, bioimaging. There are three reviews and five experimental research papers in this issue, focused around this area. Some highlights of the publications in the issue are discussed below.